2006
DOI: 10.1093/jnci/djj334
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 Overexpression and Response to Bortezomib Treatment in a Breast Cancer Model

Abstract: Cyclin D1 repression of STAT3 expression may explain the association between cyclin D1 overexpression and improved outcome in breast cancer. In addition, bortezomib can amplify the proapoptotic function of cyclin D1, raising the possibility that cyclin D1 levels may be a marker for predicting the response to this novel drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 36 publications
8
39
0
Order By: Relevance
“…Significant data concerning miRNA in MM have been reported only recently by various groups, showing signatures associated with specific molecular types and suggesting that distinct miRNAs may play an important role in neoplastic transformation and disease progression [151][152][153][154]. Experimental data have also recently suggested that miRNA-15a and miRNA-16, which are located in the 13q14 region, frequently deleted in MM, may play a role in MM cell proliferation, representing promising targets for novel therapies [155]. Novel prognostic tools are also being extensively explored, and cyclins functioning as cell cycle regulators have proved to be of interest, since overexpression of the cyclin genes CCND1, 2, and 3 are recurring abnormalities in human cancer.…”
Section: Conclusion and Perspectives Toward The Road To Cure MMmentioning
confidence: 99%
“…Significant data concerning miRNA in MM have been reported only recently by various groups, showing signatures associated with specific molecular types and suggesting that distinct miRNAs may play an important role in neoplastic transformation and disease progression [151][152][153][154]. Experimental data have also recently suggested that miRNA-15a and miRNA-16, which are located in the 13q14 region, frequently deleted in MM, may play a role in MM cell proliferation, representing promising targets for novel therapies [155]. Novel prognostic tools are also being extensively explored, and cyclins functioning as cell cycle regulators have proved to be of interest, since overexpression of the cyclin genes CCND1, 2, and 3 are recurring abnormalities in human cancer.…”
Section: Conclusion and Perspectives Toward The Road To Cure MMmentioning
confidence: 99%
“…Given that the cyclins are substrates of the proteasome, 25 we next examined MM cell cytotoxicity of P276-00 in combination with bortezomib. Increasing concentrations of P276-00 (0-1000 nM) were added with bortezomib (0-5 nM), and MM cell cytotoxicity was assayed by MTT at 24 h (Figure 5d).…”
Section: P276-00 Has Synergistic Anti-mm Activity When Combined With mentioning
confidence: 99%
“…Our data demonstrate that P276-00 overcomes the growth and survival advantage conferred by cytokines and BMSCs suggesting that it can overcome drug resistance. Given that the cyclins and Cdks are substrates of the proteasome, 25 and that proteasome inhibition may result in accumulation of these proteins conferring drug resistance, we combined bortezomib with P276-00. Our data demonstrate marked synergism of P276-00 with bortezomib.…”
Section: P276-00 Is Active In An MM Xenograft Modelmentioning
confidence: 99%
“…Because of its pivotal role in promoting cell cycle progression and, hence, cell division and proliferation, such overexpression might be expected to coincide with poor prognosis. 30,31 Overexpression of cyclin D1 has also been linked to the development of endocrine resistance in breast cancer cells. 32 Cyclin D1 overexpression is a common event in cancer, but does not occur solely as a consequence of gene amplification.…”
Section: Expression Of Apoptosis Bcl-2 and Bax In Mammary Cancer Tismentioning
confidence: 99%